Chondroitin sulfate hydrogel as well as preparation method and application thereof
By preparing chondroitin sulfate hydrogel, using amide reaction and click chemical crosslinking, the problem of chondroitin sulfate is easily hydrolyzed, achieving longer in vivo retention and stronger anti-inflammatory effects, promoting cell proliferation and collagen synthesis during tendon healing, and improving tendon repair effect.
Patent Information
- Application Number
- CN202510590970.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-09-02
AI Technical Summary
When treating tendon rupture, existing biological materials have problems such as complex synthesis process, insufficient component safety, and easy hydrolysis of chondroitin sulfate and short retention time in the body, which affects the healing effect.
By preparing chondroitin sulfate hydrogel, the CS diconjugate structure was formed using amide reaction, which enhanced molecular weight and cross-linked with 4-arm-maleimide-capped polyethylene glycol through click chemistry to form a hydrogel with larger pore size and stronger antioxidant effects.
It extends the degradation time of chondroitin sulfate in the body, improves the anti-inflammatory effect, optimizes the cell homeostasis during tendon healing, promotes cell proliferation and collagen synthesis, and improves the tendon repair speed and repair effect.
Smart Images

Figure HDA0005393168180000011 
Figure HDA0005393168180000021 
Figure HDA0005393168180000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel preparation, and particularly relates to a chondroitin sulfate hydrogel and a preparation method and application thereof. Background Art
[0002] Tendon rupture (TR) is one of the most common connective tissue injuries, but the effectiveness of clinical surgical treatment is often unsatisfactory due to large individual variability. Tendons are highly differentiated tissues, and cell stemness is a key factor affecting the healing effect after injury. Generally, the healing process after TR is divided into three overlapping phases: the inflammatory phase (characterized by infiltration of inflammatory macrophages), the proliferative phase (dominated by proliferation of tenocytes and fibroblasts and ECM deposition, mainly driven by the synthesis of type I collagen (Col I) and type III collagen (Col III)), and the remodeling phase (the Col I / III ratio gradually normalizes, and Col III is replaced by Col I and arranged in an orderly manner). During this process, prolonged inflammation, collagen deficiency, and an imbalance in the Col I / III ratio are key factors leading to poor healing (such as scar formation, tissue adhesion, and re-rupture). Therefore, an advanced method that can systematically optimize the factors related to these healing phases is urgently needed.
[0003] Over the past few decades, tissue engineering has provided new insights into tendon regeneration. Previous biomaterials (such as enzyme-mimicking metal nanoparticles, quantum dots, and hydrogels) have primarily focused on alleviating inflammation by scavenging excess reactive oxygen species. Some studies have attempted to modulate collagen synthesis by adding dipeptide hydrogels containing growth differentiation factor 5 or polycaprolactone nanofiber membranes with a balanced Col I / III ratio. However, these strategies target only a single healing factor and suffer from complex synthesis processes and insufficient ingredient safety. Therefore, strategies combining biocompatible components with multifactorial regulation hold greater promise.
[0004] As a natural component of the tendon extracellular matrix (ECM), CS has been approved for anti-inflammatory treatment and can promote fibroblast proliferation and collagen synthesis. Its macromolecular entanglement can shape the ECM topology, facilitating force transmission and signal transduction. However, CS has drawbacks such as rapid enzymatic degradation and a spatial structure that is unsuitable for cell migration. Summary of the Invention
[0005] In response to the above-mentioned deficiencies in the prior art, the present invention provides a chondroitin sulfate hydrogel, a preparation method, and an application thereof. The chondroitin sulfate is not easily hydrolyzed and has a longer retention time in the body, which can effectively solve the problems of the existing chondroitin sulfate being easily hydrolyzed and having a short retention time in the body.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0007] A method for preparing a chondroitin sulfate hydrogel comprises the following steps:
[0008] (1) preparing a chondroitin sulfate solution, adding phosphate buffer thereto, and mixing;
[0009] (2) Add NHS and EDC to the mixed solution, add cystine after full activation, stir and react, dialyze and purify after the reaction, and dry to obtain dimeric chondroitin sulfate:
[0010] (3) Dissolve the dimeric chondroitin sulfate in phosphate buffer, add tris(2-carboxyethyl)phosphine hydrochloride thereto, mix well, remove oxygen from the solution, then add 4-arm-maleimide-terminated polyethylene glycol to the solution, mix well, and dialyze to prepare chondroitin sulfate hydrogel.
[0011] Furthermore, in step (1), the volume ratio of the chondroitin sulfate solution to the phosphate solution is 75-85:15-25.
[0012] Furthermore, in step (2), the mass ratio of chondroitin sulfate, NHS, EDC and cystamine is 4.5-5.5:2-3:2.5-3.5:1.4-1.7.
[0013] Furthermore, the pH value of the phosphate buffer in step (1) and step (3) is 8.5-8.8.
[0014] Furthermore, in step (3), the mass ratio of the dimeric chondroitin sulfate, tris(2-carboxyethyl)phosphine hydrochloride (TECP-HCL) and 4-arm-maleimide-terminated polyethylene glycol (4MAL-PEG) is 54-58:1:26-30.
[0015] A chondroitin sulfate hydrogel is prepared by the above method.
[0016] The chondroitin sulfate hydrogel is used to prepare a drug for treating tendon rupture.
[0017] The beneficial effects produced by the present invention are:
[0018] In the present invention, CS and cystamine react through an amide to form a CS dimer structure. The dimer structure increases the molecular weight of CS and strengthens the physical entanglement between CS, thereby slowing its degradation rate in the body and extending the CS degradation time to 1 month. At the same time, the dimer chondroitin sulfate (CSS) responds to glutathione to cleave bonds in the body to generate reducing sulfhydryl groups, thereby enhancing the antioxidant effect and achieving a stronger anti-inflammatory effect. The optimized CS gel can synergistically intervene in tendon repair, maintain cell homeostasis by inhibiting the expression of pro-inflammatory factors and regulating macrophage polarization, thereby promoting cell proliferation, migration and collagen synthesis, and improving the repair speed and effect of tendons. Scar formation is also reduced by optimizing the ColI / III ratio. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Synthesis and characterization of ECS hydrogel, where 1A is a schematic diagram of the synthesis process, 1B is the infrared spectrum of ECS hydrogel, 1C is the hydrogen nuclear magnetic resonance spectrum of ECS hydrogel, 1D is a picture of the fluidity verification of ECS hydrogel, 1E is the cryo-electron microscopy morphology of ECS hydrogel, and 1F is a statistical diagram of the rheological properties of ECS hydrogel;
[0020] Figure 2 The performance characterization of ECS gel, among which 2A is the statistical graph of the effect of different 4MAL-PEG concentrations on viscosity, 2B is the statistical graph of the swelling of ECS gel; 2C is the statistical graph of the degradation characteristics of ECS gel, 2D is the photo of the stretching and adhesion of ECS gel; 2E is the fluorescence microscope imaging, Figure 2 F is a statistical graph of cell adhesion protein expression; 2G is a vertical fluorescence imaging graph of fluorescently stained cells; 2H is a 3D spatial graph of cell distribution within the hydrogel; 2I is a statistical graph of gene set variation analysis of cell adhesion index under different treatments; 2J is a GSVA statistical graph of the simulated ECM index;
[0021] Figure 3 Figure 3 is a characterization of the anti-inflammatory effect of ECS gel, among which 3A is a schematic diagram of the anti-inflammatory mechanism, 3B is a transmission electron microscopy image of the cell organelles; 3C is a statistical graph of the anti-inflammatory ability score, 3D is a statistical graph of the anti-aging ability score, 3E is a statistical graph of the cell growth ability score, 3F is a comparison result diagram of the LPS treatment group and the NC group, 3G is a comparison result diagram of the ACHP group and the NC group, 3H is a comparison result diagram of the CSS group and the NC group, and 3I is a comparison result diagram of the ECS group and the NC group;
[0022] Figure 4Figure 4A is a characterization of the in vitro pro-repair effect of ECS gel, where 4A is a live photo of cell migration in different treatment groups at three time points, 4B is a statistical graph of the migration rate of different treatment groups at 24 hours, 4C is a statistical graph of the migration rate of different treatment groups at 48 hours, 4D is a photo of the proliferation of different treatment groups under a fluorescence microscope, 4E is a statistical graph of the quantitative analysis results of the relative intensity of red fluorescence in different treatment groups, 4F is a fluorescent staining image of type I collagen expression in cells, 4G is a statistical graph of the quantitative analysis results of the relative fluorescence intensity of type I collagen in cells, 4H is a co-staining image of type I and type III collagen under a fluorescence microscope, 4I is a statistical graph of the relative fluorescence intensity quantitative analysis of the ratio of type I / III collagen in cells, 4J is a statistical graph of the computer scoring of the collagen synthesis level of cells in different treatment groups, and 4K is a schematic diagram of cell migration, proliferation, and collagen synthesis;
[0023] Figure 5 This is the in vivo efficacy verification of ECS gel. Figure 5A is a schematic diagram of the animal experiment timeline, 5B is the in vivo fluorescence imaging of the dye alone (IR 783) and the dye-loaded ECS gel retained in rats for 28 days; 5C is a display of the cross-sectional area of different groups, 5D is a photograph of the Achilles tendon surgery of different groups of mice, 5E is a microscopic observation of the Achilles tendon muscle fibers of different groups of mice, 5F is a quantitative graph of the relative fluorescence intensity in rats of different treatment groups at each time point, 5G is a quantitative comparative analysis of the relative fluorescence intensity in rats of different treatment groups on the 28th day; 5H is a statistical graph of the cross-sectional area of different groups, and 5I is a statistical graph of the muscle adhesion conditions of different groups. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. That is, the embodiments described are only part of the embodiments of the present invention, rather than all embodiments.
[0025] Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the invention as claimed, but is merely intended to represent selected embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative work are within the scope of protection of the present invention.
[0026] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of other identical elements in the process, method, article, or apparatus comprising the element.
[0027] The features and performance of the present invention are further described in detail below with reference to the embodiments and drawings.
[0028] Example 1
[0029] A chondroitin sulfate hydrogel, the preparation method of which comprises the following steps:
[0030] (1) Weigh 5.03 g of chondroitin sulfate and add 80 ml of ultrapure water to completely dissolve it to prepare a chondroitin sulfate solution. Then, add 20 ml of phosphate buffer (pH 8.8) to the solution and stir for 20 min.
[0031] (2) Add 2.3 g NHS and 3.1 g EDC to the mixed solution, and after 30 minutes, add 1.523 g cystine. Stir and react at 25°C for 12 hours. After the reaction, dialysis purification and freeze-drying are performed to obtain dimeric chondroitin sulfate.
[0032] (3) 400 mg of dimeric chondroitin sulfate was dissolved in ultrapure water containing 70% phosphate buffer (pH 8.8), 7.17 mg of TECP-HCL was added thereto, mixed thoroughly, and nitrogen was purged for 10 min to remove oxygen from the solution. Then, 200 mg of 4-arm-maleimide-terminated polyethylene glycol was added to the solution and mixed thoroughly. The solution was dialyzed, freeze-dried, and then renatured to obtain chondroitin sulfate hydrogel.
[0033] Example 2
[0034] A chondroitin sulfate hydrogel, the preparation method of which comprises the following steps:
[0035] (1) Weigh 5.15 g of chondroitin sulfate and add 80 ml of ultrapure water to completely dissolve it to prepare a chondroitin sulfate solution. Then, add 20 ml of phosphate buffer (pH 8.5) to the solution and stir for 20 min.
[0036] (2) Add 2.5 g NHS and 3.2 g EDC to the mixed solution, and after 30 minutes, add 1.559 g cystine. Stir and react at 20°C for 14 hours. After the reaction, dialysis purification and freeze-drying are performed to obtain dimeric chondroitin sulfate.
[0037] (3) 400 mg of dimeric chondroitin sulfate was dissolved in an aqueous solution containing 70% phosphate buffer (pH 8.8), 7.35 mg of TECP-HCL was added thereto, mixed thoroughly, and purged with nitrogen for 10 min to remove oxygen from the solution. Then, 195 mg of 4-arm-maleimide-terminated polyethylene glycol was added to the solution and mixed thoroughly. The solution was dialyzed, freeze-dried, and then renatured to obtain a chondroitin sulfate hydrogel.
[0038] Example 3
[0039] A chondroitin sulfate hydrogel, the preparation method of which comprises the following steps:
[0040] (1) Weigh 5.5 g of chondroitin sulfate and add 85 ml of ultrapure water to completely dissolve it to prepare a chondroitin sulfate solution. Then, add 15 ml of phosphate buffer (pH 8.6) to the solution and stir for 20 min.
[0041] (2) Add 3 g of NHS and 3.5 g of EDC to the mixed solution. After 30 min, add 1.665 g of cystine. Stir and react at 30°C for 10 h. After the reaction, dialysis purification and freeze-drying are performed to obtain dimeric chondroitin sulfate.
[0042] (3) 400 mg of dimeric chondroitin sulfate was dissolved in an aqueous solution containing 70% phosphate buffer (pH 8.8), 6.9 mg of TECP-HCL was added thereto, mixed thoroughly, and purged with nitrogen for 10 min to remove oxygen from the solution. Then, 207 mg of 4-arm-maleimide-terminated polyethylene glycol was added to the solution and mixed thoroughly. The solution was dialyzed, freeze-dried, and then renatured to obtain a chondroitin sulfate hydrogel.
[0043] Example 4
[0044] A chondroitin sulfate hydrogel, the preparation method of which comprises the following steps:
[0045] (1) Weigh 4.7 g of chondroitin sulfate and add 75 ml of ultrapure water to completely dissolve it to prepare a chondroitin sulfate solution. Then, add 25 ml of phosphate buffer (pH 8.7) to the solution and stir for 20 min.
[0046] (2) Add 2 g of NHS and 2.5 g of EDC to the mixed solution. After 30 minutes, add 1.423 g of cystine. Stir and react at 28°C for 13 hours. After the reaction, dialysis purification and freeze-drying are performed to obtain dimeric chondroitin sulfate.
[0047] (3) 400 mg of dimeric chondroitin sulfate was dissolved in an aqueous solution containing 70% phosphate buffer (pH 8.8), 7.0 mg of TECP-HCL was added thereto, mixed thoroughly, and purged with nitrogen for 10 min to remove oxygen from the solution. Then, 205 mg of 4-arm-maleimide-terminated polyethylene glycol was added to the solution and mixed thoroughly. The solution was dialyzed, freeze-dried, and then renatured to obtain a chondroitin sulfate hydrogel.
[0048] Example 5
[0049] A chondroitin sulfate hydrogel, the preparation method of which comprises the following steps:
[0050] (1) Weigh 4.85 g of chondroitin sulfate and add 80 ml of ultrapure water to completely dissolve it to prepare a chondroitin sulfate solution. Then, add 20 ml of phosphate buffer (pH 8.8) to the solution and stir for 20 min.
[0051] (2) Add 2.1 g NHS and 2.7 g EDC to the mixed solution, and after 30 minutes, add 1.468 g cystine. Stir and react at 23°C for 13 hours. After the reaction, dialysis purification and freeze-drying are performed to obtain dimeric chondroitin sulfate.
[0052] (3) 400 mg of dimeric chondroitin sulfate was dissolved in an aqueous solution containing 70% phosphate buffer (pH 8.8), 7.1 mg of TECP-HCL was added thereto, mixed thoroughly, and nitrogen was purged for 10 min to remove oxygen from the solution. Then, 205 mg of 4-arm-maleimide-terminated polyethylene glycol was added to the solution and mixed thoroughly. The solution was dialyzed, freeze-dried, and then renatured to obtain a chondroitin sulfate hydrogel.
[0053] Test example
[0054] 1. Taking the hydrogel prepared in Example 1 as an example, the synthesis process is shown in Figure 1 A, Results show that to obtain a biomimetic extracellular matrix (ECM)-like chondroitin sulfate (CS) hydrogel (ECS gel), CS was first modified with disulfide bonds to obtain CSS. ECS gel was constructed via a click reaction between thiolated CS (CSSH) and four-arm maleimide-terminated polyethylene glycol (4MAL-PEG).
[0055] Determine the infrared spectrum and nuclear magnetic resonance hydrogen spectrum of the hydrogel, see Figure 1 B- Figure 1 C, Figure 1 B shows the CH of the maleimide ring (944, 1348, 1408, 1468 cm -1 )、CO(1073、1247cm -1 ) and CN(2113cm -1 ) absorption peak, and 1628cm -1 In addition, the C=O / S=O stretching vibration of ECS gel 1 The H NMR spectrum shows representative peaks ( Figure 1 C), these results together confirmed the successful synthesis of ECS gel.
[0056] See the physical pictures of CSS and ECS Figure 1 D, The results show that the addition of 4MAL-PEG causes CSS to transform from a fluid state to a non-fluid hydrogel; CSS and ECS were scanned by electron microscopy, see Figure 1 E, the results show that compared with CSS, ECS gel exhibits a more significant three-dimensional (3D) network structure, and the average pore size increases from 3.90 μm to 35.38 μm; the rheological properties of CSS and CSSH are measured separately, see Figure 1 F, The results show that CSS has low mechanical strength and no gel properties (G”>G'), while the introduction of 4MAL-PEG forms a hydrogel (G'>G”), and the storage modulus of the ECS gel is significantly improved; Taken together, these results demonstrate that 3D ECS gels with larger pores were successfully constructed through the 4MAL-PEG click chemistry reaction.
[0057] 2. Performance characterization of ECS gel Figure 2 , Figure 2 A verified the effect of different 4MAL-PEG concentrations on viscosity. The results showed that when the 4MAL-PEG concentration increased from 0 to 200 mg / mL, the viscosity of ECS gel gradually increased, but when the concentration increased to 400 mg / mL, the viscosity unexpectedly decreased, which may affect its application in tendon repair.
[0058] Determine the swelling properties of ECS gel: Take 1 mL of hydrogel, record the initial weight, dry it, immerse it in ultrapure water, take it out and weigh it at different time points. Set up 3 replicates for each group, and calculate the swelling rate. Figure 2 B, The results show that the ECS hydrogel has excellent physical and chemical properties. The hydrogel maintains a progressive swelling state within 30 hours, with an average equilibrium swelling ratio of 114.5%.
[0059] Determination of the degradation performance of ECS gel: Equal weights of chondroitin sulfate dihydrate (CSS) and chondroitin sulfate gel (ECS) samples were immersed in phosphate buffer (pH 7.4), removed at predetermined time points, dried, and weighed. Each group was set up with 3 replicates, and the samples were observed for 7 consecutive days. The degradation curve was drawn. Figure 2 C, the results show that CSS degraded by 90% within 12 hours due to main chain hydrolysis, while ECS gel improved stability and prolonged functional duration by enhancing cross-linking. Figure 2 D. The results showed that ECS gel has excellent stretchability and can adhere to the tendon surface without residue, showing clinical potential.
[0060] The adhesion-related protein focal adhesion protein was used to identify the ability of ECS gel to improve cell adhesion by fluorescent staining. Tenocytes treated with normal culture medium were used as a negative control (NC), LPS-treated group was used as a positive control, and ECS gel and LPS co-treated group was used as the experimental group. All cells were washed, fixed with 4% paraformaldehyde (PFA), blocked with phosphate buffer containing 5% bovine serum albumin, permeabilized with 0.1% Triton X-100, incubated with anti-focal adhesion protein antibody, and then incubated with Alexa-Fluor-488-conjugated secondary antibody. All slides were stained with an antifade reagent containing the cell nucleus staining reagent Hoechst and mounted. Single staining and merged images were performed using a confocal microscope, and the data were analyzed using ImageJ software. Figure 2 E is a fluorescence microscope image. Figure 2 F represents the relative fluorescence intensity of green fluorescence, which represents focal adhesion protein. The results showed that the green fluorescence intensity in the positive control group was significantly reduced, indicating that LPS-mediated inflammation leads to poor cell adhesion. The experimental group, on the other hand, showed similar focal adhesion protein expression (i.e., green fluorescence intensity) to the NC group, indicating that ECS gel can reverse the poor cell adhesion state under inflammatory conditions and exhibit excellent anti-inflammatory and pro-adhesion properties.
[0061] Figure 2 GH is a characterization of the ability of ECS gel to accommodate cell shuttling inside. First, the ECS gel was spread on the bottom of a confocal microplate, and then 2 mL of tenocyte suspension (50,000 cells per mL) was added. After 6 hours of co-culture, the excess culture medium was aspirated and the gel was gently washed 3 times with PBS to remove non-adherent cells on the surface. The cells were then fixed with 4% paraformaldehyde and stained with DAPI (staining cell nuclei, blue fluorescence) and FITC-labeled phalloidin solution (staining cytoskeleton, red fluorescence) for observation under a confocal microscope. Figure 2 G is a vertical fluorescence imaging picture, Figure 2H is a 3D spatial image of the cell-ECS gel restored after scanning the gel at different layers, where the purple dots represent cells that shuttle into the gel. The results showed that after 6 hours of culture, the cells actively migrated into the interior of the hydrogel through the 3D porous network, demonstrating its biocompatibility and ability to support cell infiltration. The above findings were also verified by computer gene set variation analysis scoring ( Figure 2 IJ). These results indicate that ECS gels are an ideal platform for maintaining and enhancing cellular function under pathological conditions.
[0062] 3. Characterization of ECS gel performance and anti-inflammatory effect Figure 3 , Figure 3 A is an overview of the anti-inflammatory mechanism. The results show that inflammatory damage during tendon healing will increase the expression of pro-inflammatory markers, leading to organelle inactivation, aging and death, affecting the repair effect; LPS (1μg / mL) was used as a positive control, and ACHP, an anti-inflammatory drug available on the market, was used as a negative control. Tendon cells were cultured using CSS, ACHP, ECS and LPS, respectively. The specific culture results Figure 3 B is a transmission electron microscopy image of the cell organelles. The results showed that transmission electron microscopy (TEM) observed the shrinkage of the cell nucleus and the loss of mitochondrial cristae under inflammation, while ECS gel treatment protected these cell organelles; then Figure 3 C-3E is to evaluate and score the anti-inflammatory, anti-aging and cell growth abilities of different treatment groups through computer GSVA scoring. Figure 3 Figure F-3I shows a pairwise comparison of the different treatment groups with the normal cell group (NC group). The results show that, based on GSVA, the chondroitin sulfate treatment reversed LPS inhibition of genes and biological processes related to cell growth, signaling, and metabolism. ECS gel was the most effective in combating inflammation, with cells in the ECS gel group displaying a health state most similar to that of the normal cell group (NC group).
[0063] 4. Characterization of the in vitro pro-repair effect of ECS gel; cells were seeded in 6-well plates and scratches were created on confluent monolayer cell cultures using pipette tips. Next, cells were incubated with LPS, CSS, and ECS gels and then compared with the control group. All groups were treated with serum-free medium to block cell proliferation; the results were evaluated using optical microscopy and ImageJ at 0, 24, and 48 hours. Specific results are shown in Figure 4 A-4C; Figure 4 A is a live photo of the migration of cells in different treatment groups at three time points. Figure 4 B is the statistical graph of migration rate of different treatment groups at 24 hours. Figure 4C Statistical graph of migration rates for different treatment groups at 48 hours. The results show that tendon healing transitions from the inflammatory phase to the proliferative phase, beginning with the migration and proliferation of cells at the injury site. A scratch test revealed that LPS reduced tenocyte migration to 2.79%, while CSS (37.6%) and ECS gels (55.6%) restored migration capacity after 24 hours, with further improvement after 48 hours.
[0064] The cells treated with normal culture medium, LPS, CSS and ECS gel were incubated in EdU medium for 2 hours and then fixed with 4% paraformaldehyde. Each section was incubated with freshly prepared Click-iT TM The slides were incubated with the reaction mixture. The slides were washed twice for 5 minutes each in phosphate buffered saline containing 3% bovine serum albumin. The nuclei were stained with Hoechst 33342 for 5 minutes, and the slides were then washed with phosphate buffered saline. All steps of the EdU analysis were performed in the dark and the slides were kept moist; the results are shown in Figure 4 D-4E. Figure 4 D shows the proliferation of different treatment groups under a fluorescence microscope. Edu staining represents cells in the proliferative phase (red), and Hoechest staining represents cell nuclei (blue, used to quantify and unify cell numbers). Figure 4 E is the quantitative analysis result of relative intensity of red fluorescence in different treatment groups. The results showed that ECS gel stimulation was positively correlated with tenocyte proliferation.
[0065] The results of cell collagen synthesis are shown in Figure 4 F-4I, among them Figure 4 F is the fluorescence staining of type I collagen expression in cells (red fluorescence represents collagen, blue fluorescence represents cell nuclei). Figure 4 Figure G is the quantitative analysis result of the relative fluorescence intensity of type I collagen in cells. Figure H is the co-staining image of type I collagen and type III collagen under a fluorescence microscope (red fluorescence represents type I collagen, and green fluorescence represents type III collagen). Figure 4 I represents the quantitative analysis of the relative fluorescence intensity of the type I / III collagen ratio in the corresponding cells. The results showed that fluorescence staining and RNA sequencing indicated that collagen synthesis was impaired under LPS treatment, while ECS gel enhanced type I collagen synthesis in tenocytes and the type I / III collagen ratio in fibroblasts. Figure 4 J is the computer GSVA score for the collagen synthesis level of cells in different treatment groups. The collagen synthesis of cells in the LPS-treated inflammatory cell group was significantly inhibited, while the chondroitin sulfate treatment group (especially the ECS gel group) showed a reversal effect of inflammation-induced collagen synthesis. Figure 4 K is Figure 4A-4J Schematic representation of the conclusions. In addition to its anti-inflammatory properties, ECS gel synergistically enhances cell migration, proliferation, and collagen ratio regulation, highlighting its therapeutic potential for in vivo tendon regeneration.
[0066] 5. The results of in vivo efficacy verification of ECS gel are shown in Figure 5 , animal experiment timeline as follows Figure 5 As shown in A; experimental rats were locally injected with IR783-labeled CSS or ECS gel (n=3 / group), and the fluorescence efficiency was monitored by IVIS spectrometer at 0, 0.5, 1, 3, 5, 7, 14, 21 and 28 days. The results are shown in Figure 5 B, 5F and 5G. Figure 5 B is the in vivo fluorescence imaging image of the pure dye (IR 783) and the dye-loaded ECS gel retained in rats for 28 days. Figure 5 F is the quantitative graph of relative fluorescence intensity in rats of different treatment groups at each time point. Figure 5 G is a quantitative comparative analysis of the relative fluorescence intensity in rats from different treatment groups on day 28. The results show that the fluorescence intensity of free IR783 decreased rapidly, with almost no residue remaining on day 28, while the fluorescence of ECS gel remained significantly, indicating a longer degradation cycle.
[0067] Achilles tendon rupture (ATR) model establishment and treatment: The experiment was approved by the Animal Ethics Committee of West China Hospital, Sichuan University (ID: 20241231005). The ATR model was established in the right hind limb of 8-week-old SD rats (n = 9 / group). After Achilles tendon transection, the modified Kessler method was used for suture, and 100 μL of PBS (ATR group), CSS (CSS group), or ECS gel (ECS gel group) was locally injected. The sham-operated group (NC group) received no treatment. Specific results are shown in the table. Figure 5 C, 5H, ultrasound showed that the cross-sectional area (CSA) of the ATR group increased (0.22cm 2 , 6 weeks), while the CSA of the ECS gel group gradually approached the normal value (0.04 cm 2 ), these results indicate that ECS gel prolongs the in vivo degradation time through reasonable cross-linking, promoting functional recovery and morphological reconstruction.
[0068] The rats were killed 3 and 6 weeks after surgery, and the Achilles tendons and organs (heart, liver, spleen, lung, and kidney) were removed for histological examination. Whole blood was used for routine blood and biochemical analysis, and the results are shown in Figure 5 Results from images D and 5I show that the surface of normal AT is smooth and adhesion-free. Adhesions were most severe in the ATR group, while adhesions were reduced in the CS-related group (5D, 5G). At 6 weeks, MASSON staining revealed near-normal fiber alignment in the ECS gel group, while fibers in the ATR group were disorganized (5E). In summary, ECS gel demonstrates excellent therapeutic efficacy in AT healing, combining biocompatibility, anti-inflammatory, anti-adhesion, and collagen-regulating properties.
Claims
1. A method for preparing a chondroitin sulfate hydrogel, characterized in that: The following steps are involved: (1) preparing a chondroitin sulfate solution, adding phosphate buffer thereto, and mixing; (2) Add NHS and EDC to the mixed solution, add cystine after full activation, stir and react, dialyze and purify after the reaction, and dry to obtain dimeric chondroitin sulfate: (3) Dissolve the dimeric chondroitin sulfate in phosphate buffer, add tris(2-carboxyethyl)phosphine hydrochloride thereto, mix well, remove oxygen from the solution, then add 4-arm-maleimide-terminated polyethylene glycol to the solution, mix well, and dialyze to prepare chondroitin sulfate hydrogel.
2. The method for preparing the chondroitin sulfate hydrogel according to claim 1, wherein In step (1), the volume ratio of the chondroitin sulfate solution to the phosphate solution is 75-85:15-25.
3. The method for preparing the chondroitin sulfate hydrogel according to claim 1, wherein In step (2), the mass ratio of chondroitin sulfate, NHS, EDC and cystine is 4.5-5.5:2-3:2.5-3.5:1.4-1.
7.
4. The method for preparing the chondroitin sulfate hydrogel according to claim 1, wherein The pH value of the phosphate buffer in step (1) and step (3) is 8.5-8.
8.
5. The method for preparing the chondroitin sulfate hydrogel according to claim 1, wherein In step (3), the mass ratio of the dimerized chondroitin sulfate, tris(2-carboxyethyl)phosphine hydrochloride and 4-arm-maleimide-terminated polyethylene glycol is 54-58:1:26-30.
6. A chondroitin sulfate hydrogel, characterized in that The method according to any one of claims 1 to 5 is adopted to prepare the present invention.
7. Use of the chondroitin sulfate hydrogel according to claim 6 for preparing a drug for treating tendon rupture.